Legal clinics and people forcedly and internally displaced by natural disasters: a human rights challenge in the face of a forgotten population - Torres-Villarreal, María Lucía (2025)
The Guiding Principles on Internal Forced Displacement have established the guidelines for the management of this problem at a global level, which, far from diminishing, has increased especially in recent decades, due to natural disasters and their close relationship with climate change. The central problem is that, as it is a “soft law” norm, each State decides whether to implement it internally or not, leaving in limbo the guarantee of human rights of people who must be forcibly displaced within States, due to the disaster or as a form of preventive evacuation. The lack of knowledge or recognition by States of such displacement and its various causes, including natural disasters, has promoted legal clinics as the ideal space to make the problem visible and take action, from the structure of the clinical model, to advance in the protection of human rights of the population displaced by this cause, set guidelines for legal reflection and seek the increasingly necessary incorporation of these issues into the political, regulatory and jurisprudential agenda of States.